(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
This article aims to find out the understanding of the nature of learning and how learning helps teachers and education practitioners in designing an effective and development-oriented learning process. The research uses methods in qualitative form. The research method includes literature study by conducting literature searches related to learning and educational concepts. The main source of this research data is research articles published in scientific journals and indexed on the google scholar database. The results of the data analysis will be interpreted to explore their implications in the context of learning and education. The findings of this study are that learning and learning are two essential elements that complement each other in the educational process. Learning involves relatively permanent changes in behavior or potential behaviors as a result of experience, while learning is a more structured process designed to facilitate learning. A good integration of learning theory and learning practices in the curriculum allows students to not only acquire knowledge and skills but also develop positive attitudes and moral values. A well-designed learning design must pay attention to students’ needs, interests, and learning styles, and focus on achieving the educational goals that have been set